The influence of technological defects on the mechanical behavior of CFRP during buckling under compression based on DIC data and acoustic emission - Stanislav Slovikov; Dmitry Sergeevich Lobanov; Ekaterina Chebotareva; Valeria Melnikova (Fracture and Structural Integrity)
The research focuses on examining the impact of technological defects, specifically "dry-spot" and "wrinkles," on the mechanical behavior and buckling resistance of structural composites. The investigation of the buckling phenomenon was carried out through a compression test on a thin plate fabricated from carbon-fiber-reinforced polymer (CFRP) laminate. This test was performed using a specialized fixture designed in accordance with ASTM 3410 standard. For the analysis, the study employed a three-dimensional digital optical system, Vic-3D, in conjunction with the AMSY-6 acoustic emission system.